The Well‐Being of Slum Dwellers Are Associated With WaSH‐Related Factors: A Cross‐Sectional Study From India - P. Padma Sri Lekha; E. P. Abdul Azeez; B. Latha Lavanya; V. Kalyani; Manoj Mathew; S. Giri Prasath; J. Leo Joshwin; U. Nithyasree (Health Science Reports)
ABSTRACT Background and Aims The adverse health outcomes due to unsafe Water, Sanitation, and Hygiene (WaSH) are a public health concern in low‐and middle‐income countries. However, evidence on how WaSH is associated with psychological outcomes is minimal. Insights on this association would help address the well‐being of the slum population. Therefore, this study aimed to understand the association between knowledge, attitude and practice (KAP) of WaSH, water insecurity experiences, and sanitation‐related quality of life on the well‐being of individuals living in slums. Methods We used the KAP of WaSH, water insecurity experience scale, sanitation‐related quality of life scale, and WHO well‐being index to collect data from adult slum dwellers aged 18 years and above from Vellore, Tamil Nadu, India. We adopted a cross‐sectional study design and employed a systematic sampling procedure to select the households. The data was collected through a face‐to‐face household survey (n = 258; Male = 171; Female = 87). We employed a multiple regression model to understand the association of various factors with well‐being. Results The results indicated that a positive attitude toward WaSH and higher water insecurity experiences significantly reduced the well‐being of the slum dwellers. However, good WaSH practices (β = 0.37; 99% CI = 0.23–0.51) and sanitation‐related quality of life (β = 0.38; 99% CI = 0.25–0.50) led to good well‐being among slum‐dwellers. Also, the presence of toilets significantly contributed to the increase in well‐being and sanitation‐related quality of life. In summary, the accessibility to water sources, appropriate sanitation facilities, and hygiene practices increased the likelihood of well‐being among slum‐dwellers. Conclusion The results suggest that promoting adherence to proper WaSH practices, enhancing water security, and providing availability and access to toilet facilities for individuals living in slums are important to improving their well‐being.